How Animacy and Natural Gender Constrain Morphological Complexity: Evidence from Diachrony - Igartua, Iván; Santazilia, Ekaitz (Open Linguistics, 2018)
In addition to its central role in the organization of gender systems and its numerous effects on different parts of the grammar, animacy reveals itself as a significant, sometimes even determinant factor in diachronic processes like the reduction of morphological complexity. Complexity in the realm of inflection may be defined as the extent to which formal distinctions in paradigms are semantically or phonologically unmotivated and therefore largely unpredictable on extramorphological grounds. Animacy and natural (or sex-based) gender emerge in certain cases as features capable of constraining this kind of complexity by offering a transparent semantic criterion that helps substantiate several formal distinctions in languages, thereby reducing the amount of morphological complexity or unpredictability inherited from earlier stages in the evolution of different linguistic systems.